Edukasi Pentingnya Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) pada Anak Sekolah Dasar di SDN 101 Kendari - Mursalim; Weka Gusmiarty Abdullah; La Ode Santiaji Bande; Putu Arimbawa; Rizal Adi Saputra; Edi Syah Mihrad; Florencia Virgiane Evalyn Padang; fauzi, fitya aulia; Asrumin; Rizkah Nurhasanah; Wildayanti; Suci Oktavia Rahmadani; Ayu Pratiwi Ndibola; Marni Mulyani (Universitas Mataram, 2025)
This community service activity aimed to enhance the understanding and implementation of Clean and Healthy Living Behavior (PHBS) among elementary school students at SDN 101 Kendari. The program applied a participatory and interactive educational approach through lectures, educational videos, and direct demonstrations on proper handwashing and toothbrushing techniques. The activity involved students from grades 1 to 6 in October 2024. Evaluation results showed a 35% increase in students’ understanding of PHBS after the activity. Moreover, students demonstrated high enthusiasm, particularly during practical sessions, and teachers supported the continuation of PHBS practices in the school environment. These findings indicate that interactive health education methods effectively improve awareness and healthy habits among elementary students. Future programs are recommended to involve parents and conduct long-term evaluations to ensure sustainable behavior changes.